Differential and Inefficient Splicing of a Broadly Expressed Drosophila erect wing Transcript Results in Tissue-Specific Enrichment of the Vital EWG Protein Isoform - Koushika, Sandhya P. (American Society for Microbiology, 1999)
In this report, we document an unusual mode of tissue-enriched gene expression that is primarily mediated by alternative and inefficient splicing. We have analyzed posttranscriptional regulation of the Drosophila erect wing gene, which provides a vital neuronal function and is essential for the formation of certain muscles. Its predominant protein product, the 116-kDa EWG protein, a putative transcriptional regulator, can provide all known erect wing-associated functions. Moreover, consistent with its function, the 116-kDa protein is highly enriched in neurons and is also observed transiently in migrating myoblasts. In contrast to the protein distribution, we observed that erect wing transcripts are present in comparable levels in neuron-enriched heads and neuron-poor bodies of adult Drosophila. Our analyses shows that erect wing transcript consists of 10 exons and is alternatively spliced and that a subset of introns are inefficiently spliced. We also show that the 116-kDa EWG protein-encoding splice isoform is head enriched. In contrast, bodies have lower levels of transcripts that can encode the 116-kDa protein and greater amounts of unprocessed erect wing RNA. Thus, the enrichment of the 116-kDa protein in heads is ensured by tissue-specific alternative and inefficient splicing and not by transcriptional regulation. Furthermore, this regulation is biologically important, as an increased level of the 116-kDa protein outside the nervous system is lethal.